Etika Siswa Terhadap Guru Perspektif Ibnu Miskawaih : Studi Analisis-Deskriptif di SMK Al-Falah Nagreg Bandung - Nurhasanah, Sophia (Jurnal Riset Agama, 2023)
In the world of education, the issue of ethics is an issue that needs to be considered because the purpose of education is not only to develop humans who are knowledgeable or have cognitive intelligence alone, but also to make humans who are noble. This is the focus of this paper, which looks at ethics in the perspective of Ibn Miskawaih. This research is a qualitative research by interviewing 7 resource persons and located at SMK Al-Falah Nagreg. There are three findings in this research. First, the students of SMK Al-Falah understand enough about the study of ethics, so that they can also understand how to be ethical towards their teachers. Second, there are several ways to understand how to have good ethics according to Ibn Miskawaih, namely maintaining the balance of the three powers possessed by humans, namely the power of ratio, the power of emotion, and the power of lust. In addition, deepening religious understanding, doing good socialization and habituation, and accompanied by praise. Third, in responding to students’ ethics towards teachers, it starts with giving a sense of love towards a teacher. Some ethical principles that need to be instilled are intention, determination, diligence, obedience and respect for teachers.